Transforming local public space through hyperlocal media: A cultural community perspective - Jati, Rocky Prasetyo (Universitas Bunda Mulia, 2025)
The popularization of digital media technology, such as the Internet and various social media platforms, has allowed the general public to participate in hyperlocal media in various regions. This study aims to analyze digital hyperlocal media practices in Klaten, Central Java, from the perspective of cultural communities and community media. This study focuses on understanding how hyperlocal media becomes a means of caring for community needs, both in the production and consumption of content. In the context of preserving Javanese culture, this hyperlocal media displays five important elements: (1) the creation and existence of cultural space, (2) collective management and participation, (3) active dialogue within the community, (4) commitment to cultural preservation, and (5) continuity of cultural content. The method used is ethnographic action research with a qualitative approach to gain an in-depth understanding of hyperlocal media practices. Researchers are directly involved in the community, observing and analyzing patterns of interaction and participation. The study results show that digital hyperlocal media in Klaten functions as a local public space that is still in development. Producers and audiences are connected as members of a dynamic community and play a role in the formation of public opinion that continues to develop. In conclusion, hyperlocal media is important in preserving local culture, especially through active and ongoing community interaction in building and maintaining their cultural identity